Comparative study between herniorrhaphy alone versus hernioplasty in small-sized paraumbilical hernia - Khattab, Ahmed M.; Abdallah, Abdallah S.; Elbalshy, Mohammed A.; Albatanoney, Ayman A. (International Surgery Journal, 2019)
Background: Paraumbilical hernia is a common disease and its repair is one of the most performed surgical interventions worldwide. The most important techniques in its repair are hernioplasty and herniorrhaphy and both differ significantly. Methods: We conducted a prospective randomized controlled trial to compare hernioplasty versus herniorrhaphy alone in small-sized paraumbilical hernia as regards local wound complications e.g., seroma and wound infection in addition to recurrence rates, operation time and overall cost, by comparison between two groups each comprising 50 patients. Results: There was no significant difference between both techniques regarding hernia recurrence as well as wound complication. On the other hand, herniorrhaphy reduced significantly incision size, time of operation and overall cost. Conclusions: Our study revealed that herniorrhaphy alone is better in small-sized paraumbilical hernia repair as it showed significant correlation with decrease incision size, time of operation and overall cost.